2012
DOI: 10.1088/0031-8949/86/02/025704
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in the magnetic, optical and electrical properties of Ti0.97Co0.03O2and Ti0.97Fe0.03O2nanoparticles with Ce co-doping

Abstract: Ti0.97Co0.03O2 (TC3), Ti0.93Co0.03Ce0.04O2 (TCC34), Ti0.97Fe0.03O2 (TF3) and Ti0.93Fe0.03Ce0.04O2 (TFC34) nanoparticles were prepared by a chemical route. The x-ray diffraction pattern shows the coexistence of anatase and rutile phases and the value of the average particle size is measured using the Scherrer relation. The images from transmission electron microscopy show that the average particle size is 24, 27, 28 and 30 nm, respectively, for TC3, TCC34, TF3 and TFC34 and they are also represented by a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The variations in M S values depend on factors like shape and size of nanostructures, concentration of dopants, and lattice defects. Furthermore, an F-center exchange (FCE) mechanism has been employed to illustrate the ferromagnetism of Fe-doped ZnO nanorods [51]. In this mechanism, the…”
Section: Temperature-dependent Magnetization In Gd/znomentioning
confidence: 99%
“…The variations in M S values depend on factors like shape and size of nanostructures, concentration of dopants, and lattice defects. Furthermore, an F-center exchange (FCE) mechanism has been employed to illustrate the ferromagnetism of Fe-doped ZnO nanorods [51]. In this mechanism, the…”
Section: Temperature-dependent Magnetization In Gd/znomentioning
confidence: 99%
“…The various essential properties like thermal, electrical conductivity, optical and magnetic can be enhanced by doping rare-earth ions with alkali metals [12]. Therefore, with the substitution of rare-earth, a modification in various physical properties has been achieved (optical, magnetic).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the mechanism responsible for these states is controversial [13,14]. Recent studies have reported the sensitivity of the magnetism to the microstructure of the materials; various methods such as codoping and postannealing techniques are used to investigate the underlying mechanism [15][16][17][18][19]. In these studies, it is interesting to find that the structural defects in DMS seem to play important roles in mediating the magnetism.…”
Section: Introductionmentioning
confidence: 99%